Impact of dental trauma on oral health-related quality of life among 12 years Lucknow school children: A cross-sectional survey - Sanjukta Bagchi; Sabyasachi Saha; Vamsi Krishna Reddy; Pooja Sinha (Wolters Kluwer Medknow Publications, 2015)
Introduction: Dental trauma has become an important attribute of dental public health inducing feelings of embarrassment to smile, laugh, and show teeth affecting social relationships. Available literature regarding the impact of dental trauma on the quality of life of children in Lucknow is scarce. Aims: To assess the impact of traumatic dental injuries (TDI) on oral health-related quality of life (OHRQoL) among 12-year-old school going children of Lucknow. Materials and Methods: A cross-sectional survey was conducted among 12-year-old Lucknow school children. A total of 492 school children were selected through multistage cluster random sampling. The participants completed the child perceptions questionnaire (CPQ 11-14) - impact short form: 16 followed by an assessment of TDI. Unpaired t-test was used to determine the association of TDI with CPQ 11-14 because it involved two separate groups; one with dental trauma and other without dental trauma. Results: The prevalence of TDI was 10.8%. Maxillary central incisors (8.73%) were the frequently traumatized teeth. Enamel fracture (7.11%) was the most common type of TDI. OHRQoL had statistically significant association with TDI. Conclusions: TDI has a negative impact on OHRQoL of children affecting their personal relationships and school performance.